Conflits et tension dramatique dans le roman d’amour. L’exemple d’Orgueil et préjugé de Jane Austen - Filteau, Claude (Romanica Silesiana)
Since Jane Austen’s Pride and Prejudice, a conflict between protagonists appears to be the main event in a love novel. A crisis that such conflict results in is a source of narrative tension. Because the reader cannot anticipate the outcome of the crisis, it creates considerable suspense. The polemical confrontation, however, is mainly a dialogical component of the narrative. What Penelope Brown and Stephen Levinson call “face threatening acts” can explain the verbal strategies and emotional reactions of the heroes during their confrontation. Nonetheless, the conflict also shows that emotions rely on a particular experience of space that generates anger or fear. Depending on the context, the expression of gratitude as a polite gesture or as a way of recognizing the merit of others seems the only ethical strategy capable of ending the conflict in Jane Austen’s novel. Key words: Narrative conflict, face threatening acts, narrative tension, love novel, Jane Austen.